Strategi Komunikasi Publik Dalam Menanggapi Gelombang Misinformasi Dan Disinformasi PPDB Online Di Provinsi Banten - Gliselda Aurelia, Denis; Ema Jumiati, Ipah (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
The implementation of PPDB in Banten Province experienced several bad record findings as a result of misinformation and disinformation experienced by the public, especially for prospective registrants due to the unpreparedness of the government and several other related institutions in implementing public communication strategies. The existence of this information confusion can certainly hinder the implementation of the acceptance of new students. This phenomenon shows that the public communication strategy plays an important role in achieving an interest. The purpose of this study is to highlight public communication strategies in responding to the wave of misinformation and disinformation on the implementation of online PPDB in Banten Province. The method used in this research is a literature study with data collection techniques obtained from various sources such as books, journals, the internet, documentation, and libraries.